The Influences of Workplace Environment, Job Satisfaction and Organization Commitment on Job Performance in Manufacturing Industry - Ahmad Nur Aizat Ahmad; Md Fauzi Ahmad; Norhadilah Abdul Hamid; Nor Aziati Abdul Hamid; Norziah Ismail; Guzman Nawanir; Adnan Bakri; Mustaqqim Abdul Rahim (International Journal of Supply Chain Management, 2019)
This study was conducted to examine the influence of worker environment, organizational commitment and job satisfaction on work performance among the workers in manufacturing industry in Batu Pahat, Johor. The objective of this study is to identify the dominant influence of workplace environment, organizational commitment, and job satisfaction that effects the job performance in manufacturing industry and to determine the relationship of workplace environment, organizational commitment, and job satisfaction towards job performance. To achieve the objectives, the data were collected through a questionnaire that investigated various performance aspects. Quantitative methods used to achieve the objectives of the study. The Statistical Package for Social Science (SPSS) will be used to calculate the data obtain from the soiled questions that were presented to the respondents. The aim of this study is to train researching developers from universities in view of the transfer, interpretation and scientific knowledge. This study contributes to educate and raise awareness of management, employers, and employees. The result of this study shows there are relationship of workplace environment, organizational commitment, and job satisfaction towards job performance.